Effectiveness of Blended Learning Strategy to Improving Students' Academic Performance - Sholeh, Muh Ibnu; Habibulloh, Muh; Sokip, Sokip; Syafi’i, Asrop; ‘Azah, Nur; Munif, Munif; Sahri, Sahri (STKIP Pesisir Selatan, 2025)
Blended learning combines face-to-face instruction with online learning, designed to provide greater flexibility in the teaching and learning process. This study employs a qualitative approach with a case study method, involving students and teachers as research subjects. Data were collected through interviews, observations, and document analysis, including learning materials, exam results, and assignments given to students. The results of the study indicate that the implementation of blended learning has a positive impact on students' learning motivation, where students feel more motivated to learn independently and have the opportunity to review material at any time through online platforms. Blended learning also enhances the interaction between teachers and students, allowing students to ask questions and engage in discussions more freely. However, challenges such as limited internet access for some students and the lack of technological skills among some teachers reduce the effectiveness of this learning approach. In terms of academic performance, this study found that most students experienced improvement in their exam results and assignments after the implementation of the blended learning strategy, although some students faced difficulties in participating in online learning. Overall, blended learning proves to be effective in improving students' academic performance, as long as the existing challenges can be addressed, such as providing better internet access and offering technology training for teachers. This study suggests that Madrasah Aliyah Darunnajah Trenggalek continues to develop and utilize technology in learning to enhance the quality of education in the future.